Capturing Intravenous Thrombolysis for Acute Stroke at the ICD‐9 to ICD‐10 Transition: Case Volume Discontinuity in the United States National Inpatient Sample - Lily W. Zhou (Wiley, 2021)
Background Transition from International Classification of Diseases (ICD) Ninth and Tenth Revisions (ICD‐9 and ICD‐10) for hospital discharge data was mandated for US hospitals on October 1, 2015. We examined the volume of patients receiving thrombolysis in ischemic stroke (IS) identified using ICD codes within this transition period in the 2015 to 2016 National Inpatient Sample, a weighted 20% sample of all inpatient US hospital discharges. Methods and Results During the ICD‐10 period, 2 case identification strategies were used. Codes for IS were combined with: (1) only the ICD‐10 code for thrombolytic given into a peripheral vein and (2) all new ICD‐10 codes mapped to the ICD‐9 code for all thrombolysis. On visual inspection there was an obvious discontinuity in the volume of patients with IS treated with IV thrombolysis corresponding to 3 time periods: ICD‐9 (study period 1), transition (period 2), and ICD‐10 (period 3). With Strategy 1, analysis using a linear spline with 2 knots shows that the volume of patients with IS treated with IV thrombolysis was significantly different between study periods 1 and 2 (slope difference −1880, 95% CI −2834 to −928, P=0.005), and periods 2 to 3 (slope difference 1980, 95% CI 1207–2754, P = 0.002). With Strategy 2, volumes did not change significantly between periods 1 to 2, though there was a significant difference between periods 2 and 3 (slope difference 719, 95% CI 91–1347, P=0.034). Conclusions The significant discontinuity in thrombolysis volumes for IS during the transition period for ICD‐9 to ICD‐10 coding suggests that more rigorous validation of US administrative data during this time period may be necessary for research, resource planning, and quality assurance.